2006
DOI: 10.1143/jjap.45.2437
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser Annealing of Thin Silicon Films

Abstract: Using Monte Carlo simulations and self-consistent field (SCF) theory we study the surface and interface properties of a coarse grained off-lattice model. In the simulations we employ the grand canonical ensemble together with a reweighting scheme in order to measure surface and interface free energies and discuss various methods for accurately locating the wetting transition. In the SCF theory, we use a partial enumeration scheme to incorporate singlechain properties on all length scales and use a weighted den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 129 publications
(209 reference statements)
0
9
0
Order By: Relevance
“…In this work, we experimentally studied the influence of the impurity density and dangling-bond density on the PL properties of IV-QDs (Si-and SiC-QDs) 23) fabricated by hotion implantations into OX or quartz-glass (QZ) with very low impurities. 24,25) We evaluated the influence of the impurity density on the PL properties of IV-QDs in QZ owing to an acceptor/donor ion implantation into QZ. The I PL of IV-QDs in QZ was much smaller than that of IV-QDs in OX, but SiC-QDs in acceptor or donor doped QZ showed the I PL improvement owing to multiple-level emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we experimentally studied the influence of the impurity density and dangling-bond density on the PL properties of IV-QDs (Si-and SiC-QDs) 23) fabricated by hotion implantations into OX or quartz-glass (QZ) with very low impurities. 24,25) We evaluated the influence of the impurity density on the PL properties of IV-QDs in QZ owing to an acceptor/donor ion implantation into QZ. The I PL of IV-QDs in QZ was much smaller than that of IV-QDs in OX, but SiC-QDs in acceptor or donor doped QZ showed the I PL improvement owing to multiple-level emissions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] Numerous researches have been done for fabricating large-grained poly-Si thin films because the performance of TFTs is significantly affected by the size of the poly-Si thin films after ELC. [18][19][20][21][22][23] Until now, however, the grain size of the poly-Si thin films after ELC has usually been determined with a manual calculation. This approach included certain disadvantages such as human error and was time-consuming and exhausting.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the QCEs are reported to modulate the 2D Si band structures, and thus, to change the Si crystals to a direct band-gap material from an indirect band-gap 3D Si. 3,7,18,19) In addition, even in the Si material, PL has been observed in low-dimensional porous-Si (p-Si), 20) polycrystalline Si, 21) and even thin-film Si, 3,19,22,23) which is caused by strong QCEs. In particular, it is also reported that the T S dependence of peak photon energy is caused by the direct optical transmission in the direct band-gap thin-film Si material that is changed from the indirect band-gap bulk Si material.…”
Section: Introductionmentioning
confidence: 99%